Endoscopic Microvascular Decompression for Trigeminal Neuralgia - Ebrahim Atiah; Ahmed Adel Ayad; Mustafa Abd El-Samie Rabea (International Journal of Medical Arts, 2022)
Background: A severe, intermittent pain in the trigeminal nerve distribution area on one side of the face is known as trigeminal neuralgia. The primary pathophysiological cause of trigeminal neuralgia is neurovascular compression, which results in demyelination of the trigeminal nerve root in the cerebellopontine angle area. Endoscopes offer 360-degree views and bright lighting, making it much easier to spot and treat vascular conflicts than with conventional techniques.The Aim of the work: To evaluate the effectiveness of endoscopic microvascular decompression in patients with primary trigeminal neuralgia regarding pain control, recurrence rate and procedure-related complications.Patients and methods: The current study was applied on 12 patients with 1ry trigeminal neuralgia whom afforded to endoscopic micro-vascular decompression with mean age 59.1±9.54 years. All were submitted to clinical assessment through full history, clinical neurological examination, laboratory and imaging studies. The outcome was assessed by different scales, like visual analogue scale [VAS], pain intensity score of Barrow Neurological Institute [BNI], general and facial function scores. The follow up visits were scheduled directly after surgery, and at 3 and 6 months postoperatively.Results: The commonest affected vessel in the present study was superior cerebellar artery [SCA] [41.75%] then anterior inferior cerebellar artery [AICA] [16.7%]. Majority of patients use carbamazepine [66.7%], followed by gabapentin [58.3%]; 33% of the patients were on monotherapy and 66.7% were on combined therapy. There was significant progressive improvement of pain, general and facial function directly after surgery and till the end of follow up duration. The most common reported complication was transient unsteadiness [16.7%], with recurrence rate of 8.3% after 6 months. Conclusion: Endoscopic microvascular decompression for trigeminal neuralgia can have a promising result as regard relieving of pain with subsequent improvement of general and facial function scores with low frequency of complications and recurrence.